An extendable switched‐capacitor based three‐phase multilevel inverter with boosting capability - Hadi Aghaei; Seyed Majid Hashemzadeh; Ebrahim Babaei; Mohammad Bagher Bannae Sharifian; Atif Iqbal (IET Power Electronics, 2024)
Abstract The increasing demand for integrating renewable energy sources necessitates inverter topologies with boosting capabilities. Using inverters with boosting capability and a low number of components to integrate renewable energy sources can reduce costs. This study describes a three‐phase multilevel inverter based on extendable switching capacitors. The use of voltage‐doubling modules permits the development of the inverter's capability. By increasing the number of doubling modules, the number of output voltage levels and boost factor are increased. Furthermore, the study introduces and implements a line voltage‐based pulse width modulation approach developed for the proposed inverter. The operation of the proposed multilevel inverter, along with the pulse width modulation scheme, common mode voltage, and power loss analysis are thoroughly discussed. Additionally, a comparative analysis is provided; highlighting the advantage of reducing the number of power switches in the proposed three‐phase inverter compared to other existing topologies. Finally, a laboratory prototype is developed, operating at a 4 kHz switching frequency and with a 120 V DC‐link voltage. The experimental results corroborate the efficiency and performance of the proposed multilevel inverter, thereby validating its practical applicability.